DIALECTIC OF LEGAL THEORY IN CIVIL CASE DECISIONS FOUR COURT DECISIONS IN THE TANGERANG JURISDICTION FOR THE 2023-2025 PERIOD - Dr Walim; Ahmad Sarmadi; Agung Susilo; Uway Wahyudi (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2026)
It is not uncommon to encounter a synthesis within a new legal theory. This study analyzes four court decisions within the Tangerang jurisdiction, consisting of one court determination and three divorce rulings, using the framework of progressive legal theory, legal system theory, and the theory of justice. The objective of this research is to examine how these legal theories are reflected in judicial considerations and the consistency in the application of legal principles in similar cases. The research method employs a normative juridical approach with a qualitative analysis of the decisions of the Tangerang District Court Number 1333/Pdt.P/2025/PN.TNG, Number 926/Pdt.G/2023/PN.Tng, Number 1074/Pdt.G/2025/PN Tng, and the Tangerang Religious Court Number 1654/Pdt.G/2025/PA.Tng. The findings indicate that judges do not merely apply the law positivistically, but also consider values of justice, utility, and responsiveness to the needs of society. However, a disparity in approaches was found in assessing the weight of evidence, which has implications for whether a claim is granted or rejected. This study recommends the need for harmonization of judges' understanding regarding the theory of evidence and the principle of substantive justice.